The Prevalence of Smoking in 41-43-Year-Old Males and its Relation to Some Risk Factors - A. A. Alexandrov; M. V. Kotova; E. I. Ivanova; V. B. Rozanov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the prevalence of smoking in 41-43-year-old men living in Moscow and its association with other chronic non-communicable diseases risk factors.Material and methods. People of male sex were prospectively followed up during 32 years since childhood (11-12 years). Only 301 (30%) representatives of 1005 initially enrolled people were examined after 32 years. The examination included: survey by a standard questionnaire (the passport data, the level of physical activity, bad habits – smoking, alcohol consumption); three-time blood pressure measurement; assessment of heart rate; measurement of weight and height, thickness of skin folds (over the triceps, under the scapula and on the abdomen); waist circumference.Results. Almost 50% of 41-44-year-old males smoked every day; less than a third of the study participants had never smoked. Every fifth of the smokers smoked less than 10 cigarettes per day while more than a half of them – a pack and more. The vast majority of the past smokers (85.2%) had stopped smoking at their own will and only very few (1.2%) by doctor’s advice. The intensity of smoking according to the pack/year index was >10 in almost 81.9% of the current smokers. The past smokers had abdominal obesity significantly more often than the non-smokers and the current smokers (57.5% vs 37% and 50.7%, respectively). The current smokers revealed the significantly higher risk of hypertension. The past smokers had 2.5 times higher risk of general obesity and 2.3 times higher one – of abdominal obesity as compared to the non-smokers. The intensity of smoking at the present time correlated with heart rate (HR). The past smokers (who smoked ≥20 cigarettes/day) as compared to the non-smokers had significantly higher HR, the Quetelet index, thickness of skin fold over the triceps and on the abdomen. The currents smokers revealed correlation of the status of smoking with HR, while the past smokers – with such parameters as the Quetelet index, waist circumference, thickness of skin fold under the scapula and over the triceps and no correlation with HR. The current smokers had significantly higher the 10-year risk of death as compared to thepast smokers and the non-smokers. Conclusion. Smoking is one of the most important risk factors of development of chronic non-communicable diseases. The struggle against smoking must be promoted, while close attention should be paid to people who had stopped smoking as a group of risk of cardiovascular disease onset.